Studies on the biosynthesis of prenylated indole secondary metabolites from Aspergillus versicolor and Aspergillus sp.; and A novel approach to tumor specific drug delivery: use of a naphthyridine drug linker with a DNA hairpin - Finefield, Jennifer M., author; Williams, Robert Michael, advisor; Rovis, Tomislav, 1968-, committee member; Kennan, Alan J., committee member; Elliott, C. Michael, committee member; Thamm, Douglas H., committee member (Colorado State University. Libraries, 2011)
Herein are documented our efforts in two projects, beginning with studies toward elucidating the biosynthesis of prenylated indole alkaloids from two different Aspergillus species. Marine-derived Aspergillus sp. and terrestrial-derived Aspergillus versicolor were found to produce antipodal metabolites, in which we have developed several putative biosynthetic pathways to determine the enantio-diverging point of these fungal cultures. Through the synthesis of several potential intermediates, both with and without isotopic labeling, as well as through bioinformatics analysis of both the (-)- and (+)-notoamide biosynthetic gene clusters, significant progress has been made toward identifying a single biosynthetic precursor that serves as an intermediate to the postulated enantio-diverging event, the intramolecular hetero Diels-Alder cycloaddition. In the second project discussed, through collaboration with Dr. James Berenson at the University of California, Los Angeles, we have developed a novel tumor specific drug delivery system. Two naphthyridine-drug derivatives were synthesized and conjugated to a modified DNA oligonucleotide specifically targeted for multiple myeloma cells. The oligonucleotide-drug conjugate was successfully delivered and activated specifically within RMI8226 multiple myeloma cells.
A novel approach to tumor specific drug delivery: use of a naphthyridine drug linker with a DNA hairpin
Keywords: naphthyridine; Aspergillus